2009
DOI: 10.1128/jb.00473-09
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies Signaling Involving the Diffusible Signal Factor BDSF (cis-2-Dodecenoic Acid) Influences Virulence inBurkholderia cenocepacia

Abstract: Burkholderia cenocepacia produces a diffusible fatty acid signal molecule, cis-2-dodecenoic acid (BDSF), that has been implicated in interspecies and interkingdom communication. Here, we show that BDSF also acts as an intraspecies signal in B. cenocepacia to control factors contributing to virulence of this major opportunistic pathogen.Many bacteria use cell-cell communication systems involving the synthesis and perception of diffusible signal molecules to monitor aspects of their environment such as cell dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 27 publications
1
52
1
1
Order By: Relevance
“…Likewise, expression of the virulence regulon in Xanthomonas campestris is coregulated by the QS signal DSF and hypoxia cue (11). Interestingly, a recent study suggested that BDSF regulates virulence gene expression in B. cenocepacia independent of the AHL-type QS system (32). Given that the BDSF-dependent genes identified in that study are different from the virulence genes characterized this paper, it is a possibility that in addition to coregulation of a common set of virulence genes, BDSF and AHL may also have their own separate regulons.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, expression of the virulence regulon in Xanthomonas campestris is coregulated by the QS signal DSF and hypoxia cue (11). Interestingly, a recent study suggested that BDSF regulates virulence gene expression in B. cenocepacia independent of the AHL-type QS system (32). Given that the BDSF-dependent genes identified in that study are different from the virulence genes characterized this paper, it is a possibility that in addition to coregulation of a common set of virulence genes, BDSF and AHL may also have their own separate regulons.…”
Section: Discussionmentioning
confidence: 99%
“…B. cenocepacia has one such system and produces cis-2-dodecenoic acid in a cell density-dependent manner (19). This diffusible signal molecule alters many of the same functions controlled by cepRI, cciRI, and cepR2; mutants unable to synthesize cis-2-dodecenoic acid have decreased motility, biofilm synthesis, and virulence in the G. mellonella moth larvae and zebra fish infection models (19,44,136). This molecule may also be involved in communication between B. cenocepacia and other (19).…”
Section: Virulence Determinants Of B Cenocepaciamentioning
confidence: 99%
“…More recently, another QS signal molecule, cis-2-dodecenoic acid (BDSF), has been identified in B. cenocepacia (3). Subsequent studies showed that BDSF plays a role in the regulation of bacterial virulence (6,20). Interestingly, the two QS systems appear to act in conjunction in the regulation of B. cenocepacia virulence, as a set of the AHL-controlled virulence genes are also positively regulated by BDSF (6).…”
mentioning
confidence: 99%